The Influence of Monetary Savings, Service Quality, Brand Image, Word of Mouth and Convenience on Purchase Intention in the Hypermarket Scale Retail Industry - Syah, Tantri Yanuar Rahmat; Putri Utami, Sari (Profesional Muda Cendekia Publishing, 2024)
Research Aims: Purchase intention is an important thing for companies to understand because understanding consumer desires is an effective strategy so that companies can correctly determine marketing strategies, gain profits and strengthen their market position amidst the competitive red ocean market of modern retail business. The aim of this research is to identify the influence of monetary savings, convenience, service quality, brand image and word of mouth (WOM) on purchase intentions, as well as identifying the influence of convenience on service quality, as well as the relationship between service quality and brand image on WOM. Design/methodology/approach: This research used a purposive sampling method involving 353 consumers of Hypermart/Transmart/Lotte Mart stores in the Jabodetabek area. Data were analyzed using Structural Equation Model (SEM) with SmartPLS 3.0.. Research Findings: Some of the findings in this research are that monetary savings, convenience, brand image have an influence on purchase intention, but service quality and word of mouth have no influence on purchase intention. The next conclusion is that brand image influences WOM, then comfort influences service quality, but service quality does not influence WOM. Theoretical Contribution/Originality: The managerial implication of this research is that the management of modern hypermarket scale retail store companies can increase purchasing intentions by providing sales promotions that display monetary savings factors, increasing comfort and brand image so as to maintain the existence of the Red Ocean market. Keywords: purchase intention, monetary savings, convenience, service quality, brand image, word of mouth